Antibacterial Activity of a Lytic Enzyme Encoded by Pseudomonas aeruginosa Double Stranded RNA Bacteriophage phiYY - Yang, Yuhui; Le, Shuai; Shen, Wei; Chen, Qian; Huang, Youying; Lu, Shuguang; Tan, Yinling; Li, Ming; Hu, Fuquan; Li, Yang (Frontiers in Microbiology, 2018)
Multidrug-resistant Pseudomonas aeruginosa is one of the most life-threatening pathogens for global health. In this regard, phage encoded lytic proteins, including endolysins and virion-associated peptidoglycan hydrolases, have been proposed as promising antimicrobial agents to treat P. aeruginosa. Most dsDNA phages use virion-associated peptidoglycan hydrolases to degrade peptidoglycan during infection, and endolysin to lyse the host cells at the end of lytic cycle. By contrast, dsRNA phage encodes only one lytic protein, which is located in the viral membrane to digest the peptidoglycan during penetration, and also serves as an endolysin to release the phage. Currently, there are only seven sequenced dsRNA phages, and phiYY is the only one that infects human pathogen P. aeruginosa. In this study, dsRNA phage phiYY encoded lysin, named Ply17, was cloned and purified. Ply17 contains a PG-binding domain and a lysozyme-like-family domain. Ply17 exhibited a broad antibacterial activity against the outer membrane permeabilizer treated Gram-negative bacteria. The best lytic activity was achieved at 37°C, pH 7.5, in the presence of 0.5 mM EDTA. Moreover, it could effectively lyse Gram-positive bacteria directly, including Staphylococcus aureus. Therefore, dsRNA phage encoded Ply17 might be a promising new agent for treating multidrug-resistant pathogens.